Early-onset bipolar disorder: a family treatment perspective. - Miklowitz, D; Biuckians, A; Richards, J (2006)
Mood disorder symptoms and their associated functional impairments are hypothesized to come about as the result of the conjoint, interactive influences of genetic, biological, and psychological vulnerabilities, family distress, and life stress at different points of development. We discuss a developmental psychopathology model that delineates pathways to high family conflict and mood exacerbation among early-onset bipolar patients. New data from a treatment development study indicate that adolescent bipolar patients in high expressed emotion families have more symptomatic courses of illness over 2 years than adolescents in low expressed emotion families. Chronic and episodic stressors are also correlated with lack of mood improvement while adolescents are in treatment. Family-focused treatment (FFT) given in conjunction with pharmacotherapy appears to ameliorate the course of bipolar disorder in adults. This treatment has recently been modified to address the developmental presentation of bipolar disorder among adolescents. We present data from an open trial of FFT and pharmacotherapy (N = 20) indicating that bipolar adolescents stabilize in mania, depression, and parent-rated problem behaviors over 2 years. Future research should focus on clarifying the developmental pathways to early-onset bipolar disorder and the role of protective factors and preventative psychosocial interventions in delaying the first onset of the disorder.